The epidemiological and clinicopathological study of benign breast disease with special reference to treatment regimen - Jaiswal, Anand Kumar; Saxena, Rakesh; Kumar, Shesh (International Surgery Journal, 2017)
Background: Benign breast disease can be defined to include all those breast diseases which are not malignant. The diagnostic dilemma is for the disease like atypical ductal hyperplasia, mammary intra epithelial neoplasia, ductal carcinoma in situ and lobular carcinoma in situ. Methods: An epidemiological study of 78 patients of benign breast diseases who attend the surgery OPD or admitted as indoor patients in the department of general surgery, B.R.D. Medical College Gorakhpur during a period of one year. Results: Benign breast diseases were most common in third decade (51.28%) following fourth decade (23.07%) of life. Most of the patients belongs to middle (37.1%) and higher (32.5%) socioeconomic status. Fibroadenosis (34.61%) was found to be commonest lesion followed by fibroadenoma (26.92%) and mastitis (24.35%). Conclusions: In our study of benign breast disease, breast pain was the commonest presenting symptom (64.01%) followed by lump in the breast (42.3%). The final diagnosis of benign breast lesion in descending order was fibroadenosis (34.6%), fibroadenoma (26.9%), mastitis (24.4%), duct ectasia (3.8%) and dermatitis of nipple, gynaecomastia 2.56% each. Only one case each (1.2%) of cystosarcoma phyllode, duct papilloma, tuberculosis and galactocele was seen.